A Mal functional variant is associated with protection against invasive pneumococcal disease, bacteremia, malaria and tuberculosis. - Khor, C; Chapman, S; Vannberg, F; Dunne, A; Murphy, C; Ling, E; Frodsham, A; Walley, A; Kyrieleis, O; Khan, A; Aucan, C; Segal, S; et al. (2007)
Toll-like receptors (TLRs) and members of their signaling pathway are important in the initiation of the innate immune response to a wide variety of pathogens. The adaptor protein Mal (also known as TIRAP), encoded by TIRAP (MIM 606252), mediates downstream signaling of TLR2 and TLR4 (refs. 4-6). We report a case-control study of 6,106 individuals from the UK, Vietnam and several African countries with invasive pneumococcal disease, bacteremia, malaria and tuberculosis. We genotyped 33 SNPs, including rs8177374, which encodes a leucine substitution at Ser180 of Mal. We found that heterozygous carriage of this variant associated independently with all four infectious diseases in the different study populations. Combining the study groups, we found substantial support for a protective effect of S180L heterozygosity against these infectious diseases (N = 6,106; overall P = 9.6 x 10(-8)). We found that the Mal S180L variant attenuated TLR2 signal transduction.